Kesesuaian Geometrik Jalan Ditinjau dari Aspek Alinyemen Horizontal dengan Metode Bina Marga: (Studi Kasus : Jl. Padang-Solok Kelurahan Indarung, Kec. Lubuk Kilangan, Kota Padang, Prov. Sumatera Barat) - Hengki Rolando Sirait; Fajrin Fajrin (Pusat riset dan Inovasi Nasional, 2024)
Padang-Solok Road, which has uphill road conditions and sharp corners, makes this road a lot of accidents. Apart from the negligence of motorists, accidents in this area are also caused by geometric factors of the road. The purpose of this study is to determine the suitability or not of road geometry in terms of horizontal alignment with the Highways method. This type of research is descriptive quantitative. It was found thatthe existence of the existing situation after being concluded from the approach of the experience of going into the field is that the road has a fairly extreme slope where the road on the left if it leads to Solok has a fairly high slope. And the existing suitability with clan building has several differences, discrepancies and gaps both intentional due to road conditions and elements of accident.